Towards a Cutting-Edge Criteria for Aggressive Driving Behavior Recognition - Costa, Lucas; Branco, Kalinka (Anais do Workshop Latinoamericano de Dependabilidade e Segurança em Sistemas Veiculares (SSV); 2025: Anais do II Workshop Latinoamericano de Dependabilidade e Segurança em Sistemas Veiculares, 2025)
Driver behavior (DB) plays an important role in both road safety and vehicle energy management. Better understanding of how drivers respond to actual driving environments, as well as how their driving style affects road traffic safety, fosters the development of driver behavior monitoring systems that enhance Intelligent Transportation Systems (ITS). However, a literature review shows a lack of integrated and robust systems capable of providing reliable driving assistance in the field that accounts for the uniqueness in driving style and risk profiling assessments. This work aims to showcase a research taxonomy1 for aggressive driving behavior recognition, which relies on a context-aware, personalized, and real-time assessment. These findings will be used to highlight the importance of incorporating contextual and personalized assessments into driver behavior monitoring systems, paving the way for more intelligent and proactive driving assistance solutions.